Analysis of the relationship between the predicted biological activity and the chemical structure of S-derivatives of 5-(5-bromofuran-2-yl)-4R-1,2,4-triazole-3-thiols - O. A. Bigdan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
1,2,4-Triazole derivatives are actively used as components in the development of new drugs, plant protection products, polymeric materials, anti-corrosion agents and etc. Chemical modeling of substituted 1,2,4-triazoles due to the introduction of different pharmacophores into the structure is very popular among scientists in various fields. Today it is known that some S-derivatives of 5-(5-bromofuran-2-yl)-4R-1,2,4-triazole-3-thiols have antimicrobial activity.